AZAS “PRESUMPTION OF INNOCENCE” ATAU AZAS” PRADUGA TAK BERSALAH” DI NEGARA HUKUM INDONESIA SEBUAH PEMAHAMAN EMPIRIK - Kosmas Minggu, (Journal of Innovation Research and Knowledge, 2024)
The purpose of this study is to discuss the phenomena that occur in Indonesian human rights originating from the nation's philosophy and view of life, namely Pancasila. This is in the Preamble and Body of the 1945 Constitution in Article 1 paragraph (3) as a state law. Which includes all human rights in the fields of law, politics, economics and socio-culture. While the existence of the Principle, Presumption, Of Innocence or the principle of the presumption of innocence is one aspect that is included in this goal. Therefore, the scope of the problem presented is simple, namely how the existence of the presumption of lawlessness has been implemented, both by law enforcement, the mass media, as well as by "man in the street or the community in law enforcement in our beloved state of law." this. In Indonesian criminal procedure law, it is known as a principle that is closely related to the human rights of the accused in criminal cases, namely the principle of presumption of innocence in the Indonesian state of law, namely to provide protection to every Indonesian citizen from criminal acts. by arbitrary authorities against the accused so that it is possible for human rights to enjoy dignity as human beings is the main goal "While the existence of the presumption of innocence is one of the aspects included in this goal, namely whether this has been implemented, whether law enforcement , the mass media, as well as by the general public in this country of law. Because before the accused or suspect was tried by the court as the agency that revealed his guilt, it turned out to have been tried first by the general public or the press, this is better known as: "trial by the press". hear about acts of vigilante action by community members against someone who has just been suspected of committing a criminal act. In implementing the law in the State of Indonesia honestly, the principle of the presumption of innocence has not been carried out in a firm, consistent, dedicated and responsible manner by law enforcers, the mass media and the general publicThe purpose of this study is to discuss the phenomena that occur in Indonesian human rights originating from the nation's philosophy and view of life, namely Pancasila. This is in the Preamble and Body of the 1945 Constitution in Article 1 paragraph (3) as a state law. Which includes all human rights in the fields of law, politics, economics and socio-culture. While the existence of the Principle, Presumption, Of Innocence or the principle of the presumption of innocence is one aspect that is included in this goal. Therefore, the scope of the problem presented is simple, namely how the existence of the presumption of lawlessness has been implemented, both by law enforcement, the mass media, as well as by "man in the street or the community in law enforcement in our beloved state of law." this. In Indonesian criminal procedure law, it is known as a principle that is closely related to the human rights of the accused in criminal cases, namely the principle of presumption of innocence in the Indonesian state of law, namely to provide protection to every Indonesian citizen from criminal acts. by arbitrary authorities against the accused so that it is possible for human rights to enjoy dignity as human beings is the main goal "While the existence of the presumption of innocence is one of the aspects included in this goal, namely whether this has been implemented, whether law enforcement , the mass media, as well as by the general public in this country of law. Because before the accused or suspect was tried by the court as the agency that revealed his guilt, it turned out to have been tried first by the general public or the press, this is better known as: "trial by the press". hear about acts of vigilante action by community members against someone who has just been suspected of committing a criminal act. In implementing the law in the State of Indonesia honestly, the principle of the presumption of innocence has not been carried out in a firm, consistent, dedicated and responsible manner by law enforcers, the mass media and the general public